Weather Forecasting Using Sliding Window Algorithm. (10th December 2013) - Kapoor, Piyush; Bedi, Sarabjeet Singh
Abstract : To predict the future's weather condition, the variation in the conditions in past years must be utilized. The probability that the weather condition of the day in consideration will match the same day in previous year is very less. But the probability that it will match within the span of adjacent fortnight of previous year is very high. So, for the fortnight considered for previous year a sliding window is selected of size equivalent to a week. Every week of sliding window is then matched with that of current year's week in consideration. The window best matched is made to participate in the process of predicting weather conditions. The prediction is made based on sliding window algorithm. The monthwise results are being computed for three years to check the accuracy. The results of the approach suggested that the method used for weather condition prediction is quite efficient with an average accuracy of 92.2%.